THE IMPACT OF BUDGET EFFICIENCY, ACCOUNTABILITY, AND FINANCIAL TRANSPARENCY ON THE EFFECTIVENESS OF PUBLIC ACTIVITY IMPLEMENTATION: EVIDENCE FROM THE KELILING DANAU DISTRICT OFFICE, KERINCI REGENCY - Novita Nova; Laynita Sari (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to analyze the effect of budget efficiency, accountability, and financial transparency on the effectiveness of activity implementation at the Keliling Danau District Office, Kerinci Regency. This research employs a quantitative approach using survey methods through questionnaires distributed to respondents. The results indicate that partially, budget efficiency and accountability do not have a significant effect on the effectiveness of activity implementation, while financial transparency has a positive and significant effect. Simultaneously, budget efficiency, accountability, and financial transparency significantly influence the effectiveness of activity implementation, with a contribution of 93.9%. These findings highlight that financial transparency plays a dominant role in improving the effectiveness of public sector activities.